Determining forward speed from accelerometer jiggle in aquatic environments - Cade, D. E.; Barr, K. R.; Calambokidis, J.; Friedlaender, A. S.; Goldbogen, J. A. (The Journal of Experimental Biology, 2018)
How fast animals move is critical to understanding their energetic requirements, locomotor capacity and foraging performance, yet current methods for measuring speed via animal-attached devices are not universally applicable. Here, we present and evaluate a new method that relates forward speed to the stochastic motion of biologging devices as tag jiggle, the amplitude of the tag vibrations as measured by high sample rate accelerometers, increases exponentially with increasing speed. We successfully tested this method in a flow tank using two types of biologging devices and in situ on wild cetaceans spanning ~3 to >20 m in length using two types of suction cup-attached tag and two types of dart-attached tag. This technique provides some advantages over other approaches for determining speed as it is device-orientation independent and relies only on a pressure sensor and a high sample rate accelerometer, sensors that are nearly universal across biologging device types.